Modelling the Production Planning in the case of Production and Asset Constraint Considering the Rejected and Recycled Product keeping Centres (Case Study: Water Pump Producer) - Seidi, Masoud; Jamshidnia, Mehdi (Ciência e Natura, 2015)
This study aims to provide a general modelling for production planning and the supply chain control in a large scale, in which the asset constraint and places for recycling and junking are added to the issues of production and capacity limitations of the company. Accordingly this study includes the optimization of production process besides the supply chain control proposes and the feasibility of recycle centres in order to decrease the production expense and having more profitability, which finally lead to the customer satisfaction and production system efficiency. The objective function of the model includes the optimization of the expenses on some matters such as establishment of recycling centres, production, accumulation centres, recycling and junking, warehousing, orders and transportations expenses. To estimate the model it is applied on a company which produces water pumps with different powers. The results revealed that the total expense of the system was increased in a period of 12 months related to the expense on establishment of recycle centres, while in a period of 48 month not only the money put into the recycle centres was returned, but also the production cost of each pump was totally decreased for 11 unites. This decline in the total expenses was due to the balance made by using the recycled materials instead of the new raw materials. To sum up, the more factories in which recycled materials are used, the less expenditure is predicted for system in all.